Produção enxuta aplicada à construtoras de pequeno e médio porte - Arantes, Vitor Soares Rezende [UNESP] (2015)
Against the current need of improvements in construction processes and increased competitiveness on Construction Industry in Brazil, lean construction concepts have spread all over the market, achieving small and medium enterprises. In reason of this, the monograph it is a research based on interviews of small and medium construction enterprises from Vale do Paraíba, São Paulo, Brazil, that focus in identify practices of lean construction implementation and barriers to incorporate these concepts on them. Besides the research, it will be done an analysis and some suggestions to overcome the obstacles appeared